Dynamic Soil Compaction–recent Methods and Research Tools for Innovative Heavy Equipment Approaches. (2015) - Pankrath, Holger; Barthel, Marco; Knut, Alexander; Bracciale, Matteo; Thiele, Ralf
Abstract: An efficient soil compaction is necessary for a large number of construction projects. Therefore the optimization and improvement of heavy equipment working fast and uniformly from the surface is an important research and development field all over the world. A group of civil and mechanical engineers of the Leipzig University of Applied Sciences supported by national and international partners is working on this topic since September 2012. With innovative scaled tests using optical high-speed methods, numerical simulations in ABAQUS and field tests with real equipment, the group created conditions for proofing and linking the approaches of optimization and new development of innovative heavy equipment for soil compaction.